Analisis Semiotika Lirik Lagu Tanah Pusako (Jurnal Ilmu Komunikasi dan Bisnis, 2023)
The analysis of this study uses the semiotic analysis of Roland Barthes' model with the use of two-stage significance, namely denotative meaning and connotative meaning. The results that the denotation meaning or the real meaning of Tanah Pusako (inheritance landis) the land where women live in the Minangkabau custom which is inhabited for generations by women. Meanwhile, the connotative or additional meaning of Tanah Pusako is the place where women live for generations, so the additional meaning is that pusako property is an inheritance from the Minangkabau people so that the ownership is not private but belongs to the people so it is forbidden to sell it. As for the myths or culture that has become the ideology or belief of the people regarding Pusako Land is land that belongs to the people so it is not privately owned if someone sells the pusako land, there will be many calamities befalling the person selling the pusako land (among them, will experience poverty, calamity , or being sworn in by the former ancestors who occupied Tanah Pusako so that they will experience a lot of suffering in life).